2018
DOI: 10.1002/acn3.627
|View full text |Cite
|
Sign up to set email alerts
|

Seizures, periodic and rhythmic patterns in primary intraventricular hemorrhage

Abstract: ObjectivePrimary intraventricular hemorrhage (pIVH) uncommonly presents with seizures. There are no prior data regarding the frequency of seizures, periodic and rhythmic patterns on continuous electroencephalography (EEG), (cEEG) in these patients.MethodsWe retrospectively assessed frequency of seizures, periodic discharges, and rhythmic patterns in pIVH patients undergoing cEEG monitoring. We reviewed indications for cEEG, demographics, GCS at presentation and during cEEG, modified Graeb score (mGS), presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Similar ndings were reported in a cohort of patients with intraventricular (IVH) or intraparenchymal hemorrhage (IPH). Among 11 patients with IVH, 64% had PRP compared to 38% of 32 patients with IPH 20 . Small studies in children have shown associations of LPDs, BIPDs, and GPDs with acute structural abnormalities (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…Similar ndings were reported in a cohort of patients with intraventricular (IVH) or intraparenchymal hemorrhage (IPH). Among 11 patients with IVH, 64% had PRP compared to 38% of 32 patients with IPH 20 . Small studies in children have shown associations of LPDs, BIPDs, and GPDs with acute structural abnormalities (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…The volume of IVH is a significant predictor of poor outcome. [2][3][4] Apart from that, rapid neurological deterioration can be a consequence of acute blockage of the cerebrospinal fluid (CSF) circulation, the mass effect caused by the hematoma, sudden increase in intracranial pressure, and reduced cerebral perfusion. Additionally, IVH causes mechanical disruption, ventricular wall distension, hypertensive hydrocephalus, and toxic metabolic damage to the ependyma.…”
Section: Introductionmentioning
confidence: 99%